THE POLISH NATIONAL MINORITY AND ITS SACRED ARCHITECTURE IN THE REPUBLIC OF SRPSKA - Miroslav Malinović; Milijana Okilj; Ljubiša Preradović (AGG+, 2016)
The topic of this paper is the arrival of the Polish national minority to the territory of today’s Republic of Srpska and the architecture of its sacred buildings. The Poles colonized Bosnia and Herzegovina shortly after the Austro-Hungarian Empire had occupied this territory in 1878. The Poles, like many other colonized minorities, built churches that served not only as  sacred buildings, but as monuments to their culture, language, and national identity as well. After WWII, the majority of the Poles were repatriated, with the highest rate among all minorities in former Yugoslavia. Many of their churches, which are the topic of this paper, were demolished during and after WWII, with only one remaining northern from Banja Luka.